2019
DOI: 10.1186/s13148-019-0711-4
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase SMYD2: ubiquitous regulator of disease

Abstract: SET (Suppressor of variegation, Enhancer of Zeste, Trithorax) and MYND (Myeloid-Nervy-DEAF1) domain-containing protein 2 (SMYD2) is a protein methyltransferase that methylates histone H3 at lysine 4 (H3K4) or lysine 36 (H3K36) and diverse nonhistone proteins. SMYD2 activity is required for normal organismal development and the regulation of a series of pathophysiological processes. Since aberrant SMYD2 expression and its dysfunction are often closely related to multiple diseases, SMYD2 is a promising candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 84 publications
(154 reference statements)
1
77
0
Order By: Relevance
“…Protein methylation usually occurs on lysine or arginine, and both histones and nonhistone proteins can be methylated [ 104 – 106 ]. A plethora of studies have demonstrated that protein methylation plays an important role in cell survival/death and diseases [ 104 , 107 109 ], but the research on their roles in ferroptosis is in its infancy. For example, lysine demethylase 3B (KDM3B), a histone H3K9 demethylase, inhibits erastin-induced ferroptosis by cooperating with the transcription factor activating transcription factor 4 (ATF4) to upregulate SLC7A11 expression [ 110 ] ( Figure 4 ).…”
Section: Posttranslational Modifications (Ptms) In Ferroptosismentioning
confidence: 99%
“…Protein methylation usually occurs on lysine or arginine, and both histones and nonhistone proteins can be methylated [ 104 – 106 ]. A plethora of studies have demonstrated that protein methylation plays an important role in cell survival/death and diseases [ 104 , 107 109 ], but the research on their roles in ferroptosis is in its infancy. For example, lysine demethylase 3B (KDM3B), a histone H3K9 demethylase, inhibits erastin-induced ferroptosis by cooperating with the transcription factor activating transcription factor 4 (ATF4) to upregulate SLC7A11 expression [ 110 ] ( Figure 4 ).…”
Section: Posttranslational Modifications (Ptms) In Ferroptosismentioning
confidence: 99%
“…Most of the data concerning the relationship between SMYD2 and the immune system refer to its methyltransferase activity on histone 3 lysine 36 (H3K36) (Brown et al 2006). Nonetheless, SMYD2 enzymatic activity is not restricted to H3K36, and this enzyme can also act on histone 4 lysine 20 (H4K20), among other targets (Boehm et al 2017;Yi, Jiang, and Fang 2019).…”
Section: Smyd2mentioning
confidence: 99%
“…These enzymes act on histone and nonhistone targets to regulate many biological processes, including muscle development and cancer (Spellmon et al 2015). Indeed, SMYD2 (Yi, Jiang, and Fang 2019) and SMYD3 (Bottino et al 2020) are considered to have oncogenic properties in a myriad of cancer types, although they are dispensable for normal mouse development and adult life, probably due to its redundancy (Bagislar et al 2016). In addition, SMYD proteins are very important for muscle physiopathology (Du, Tan, and Zhang 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SMYD2 is essential for normal organismal development and dysregulation of SMYD2 was found in cardiovascular disease and cancer . For example, SMYD2 is significantly overexpressed in many cancers including esophageal squamous cell carcinoma (ESCC), bladder and gastric cancer, and in triple negative breast cancer it was shown to have a tumor promoting effect . In some cases, the molecular mechanisms connecting the methylation of SMYD2 non‐histone substrates and oncogenic effects have been discovered and, based on these, inhibitors of SMYD2 have been tested as therapeutic agents …”
Section: Introductionmentioning
confidence: 99%